A Perspective on the Concept of Economic Inequality in the 21st Century (International Journal of Applied Research in Management and Economics, 2020)
This article aims to make an analysis on how the new reconfiguration of the global economic order, where the EU is one of the three main actors, most likely based on strong protectionist tendencies, affects the EU's ability to support more intense national economic policies and stricter rules aimed at reducing economic and social disparities. Our analytical study, one with an interdisciplinary character because, although the investigated aspects fit mainly in the economic sphere, they also have important and relevant connections with the field of international relations, follows four directions of investigation on opinions projected around the issue of economic inequality and its measurement. At the same time, the ideas around which we have built this material come to certify the already expressed views of economists that the reduction of major economic inequalities is not achieved strictly by economic measures but through a combination of factors, such as political and social programs or diplomacy. Also, our analysis brings to the foreground one of the most used instruments of measuring economic inequality, the Gini Coefficient. A series of conclusions resulted from this segment of our research, based on the interpretation of recent official statistics and data regarding economic inequality measured within the EU, illustrate the advantages and disadvantages of measuring such complex economic phenomena and what are the dangers that economists face when assigning certain figures to countries on the globe.